Pengaruh Marketing Mix dan Electronic Word Of Mouth terhadap Consumer Satisfaction pada E-Commerce Shopee Live: Studi pada Konsumen The Originote di Kota Surabaya - Yanti Grace Hutasoit; Sonja Andarini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The current developmentsof technology and digital transformation has brought significant changes, particularly in the context of shopping. Likewise, in the competitive beauty industry, The Originote, the subject of this research, has successfully utilized the Shopee Live e-commerce platform as a means of marketing its products.sThis study aimssto identify and understandsthe Influence of Marketing Mix and Electronic Word of Mouth on Consumer Satisfaction in Shopee Live E-commerce (A Study on The Originote Consumers in Surabaya). The research method is quantitative, employing a questionnaire distributed to 160 respondents. The research population consists of The Originote product consumers residing in Surabaya in 2023, selected through purposive sampling. The data analysis method used is multipleslinear regression withsSPSS 25 forsWindows. The results of this study are as follows: 1) The marketing mix variables, including product, price, promotion, place, and electronic word of mouth, collectively influence consumer satisfaction simultaneously. 2) Product has a positive but non-significant partial effect on consumer satisfaction. 3) Price has a significant positive partial effect on consumerssatisfaction. 4) Promotion has a non-significant negative partial effect on consumer satisfaction. 5) Place has a positive but non-significant partial effectson consumrssatisfaction. 6) ElectronicsWord of Mouth has a significant positive partial effect on consumerssatisfaction.